2006
DOI: 10.1248/jhs.52.758
|View full text |Cite
|
Sign up to set email alerts
|

Effect of .BETA.-Crytoxanthin on Circulating Bone Metabolic Markers: Intake of Juice (Citrus Unshiu) Supplemented with .BETA.-Cryptoxanthin Has an Effect in Menopausal Women

Abstract: The effects of prolonged intake of juice prepared from Satsuma mandarin (Citrus unshiu MARC.) containing β-cryptoxanthin on circulating biochemical markers of bone metabolism in subjects, including menopausal woman, were investigated. Ninety volunteers, aged 27-65 years (19 men and 71 women), were enrolled in this study. The 71 females included 35 premenopausal women (ages, 27-50 years) and 36 postmenopausal women (ages, 46-65 years). Volunteers were divided into four groups; placebo juice without β-cyptoxanth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 36 publications
1
37
0
Order By: Relevance
“…It has been reported that the serum concentration of β-cryptoxanthin increased due to the consumption of vegetable juice in women from 1.3 × 10 −7 to 5.3 × 10 −7 M. 24) In ninety volunteers (aged 27-65 years), serum bone-specific alkaline phosphatase activity was significantly increased after the intake of juice containing β-cryptoxanthin (3.0 or 6.0 mg/day) for 56 days as compared with the value obtained before intake. 51) γ-Carboxylated osteocalcin concentration was significantly increased after the intake of juice containing β-cryptoxanthin (3.0 or 6.0 mg/day) for 28 or 56 days as compared with the value obtained before intake or after the intake of placebo juice. 51) Serum TRACP activity and type I collagen N-telopeptide concentration were significantly decreased after the intake of juice containing β-cryptoxanthin (3.0 or 6.0 mg/day) for 28 or 56 days as compared with the value obtained before intake or after intake of placebo juice, and significant decreases were also seen after the intake of 1.5 mg/day β-cryptoxanthin as compared with the value obtained before intake.…”
Section: Effects Of β-Cryptoxanthin In Healthy Individuals and Menopamentioning
confidence: 81%
See 3 more Smart Citations
“…It has been reported that the serum concentration of β-cryptoxanthin increased due to the consumption of vegetable juice in women from 1.3 × 10 −7 to 5.3 × 10 −7 M. 24) In ninety volunteers (aged 27-65 years), serum bone-specific alkaline phosphatase activity was significantly increased after the intake of juice containing β-cryptoxanthin (3.0 or 6.0 mg/day) for 56 days as compared with the value obtained before intake. 51) γ-Carboxylated osteocalcin concentration was significantly increased after the intake of juice containing β-cryptoxanthin (3.0 or 6.0 mg/day) for 28 or 56 days as compared with the value obtained before intake or after the intake of placebo juice. 51) Serum TRACP activity and type I collagen N-telopeptide concentration were significantly decreased after the intake of juice containing β-cryptoxanthin (3.0 or 6.0 mg/day) for 28 or 56 days as compared with the value obtained before intake or after intake of placebo juice, and significant decreases were also seen after the intake of 1.5 mg/day β-cryptoxanthin as compared with the value obtained before intake.…”
Section: Effects Of β-Cryptoxanthin In Healthy Individuals and Menopamentioning
confidence: 81%
“…51) A significant increase in serum β-cryptoxanthin concentration was also observed at 28 days at the end of intake, indicating that the carotenoid is stable in the serum. Serum β-cryptoxanthin concentration was in the range of 4.20 × 10 −7 M to 4.89 × 10 −7 M in the placebo groups.…”
Section: Effects Of β-Cryptoxanthin In Healthy Individuals and Menopamentioning
confidence: 87%
See 2 more Smart Citations
“…Moreover, the intake of ß-cryptoxanthin-reinforced juice for long periods of time was shown to have both stimulatory effects on osteoblastic bone formation and inhibitory effects on osteoclastic bone resorption in healthy humans and in postmenopausal women, as assessed by serum biochemical markers of bone metabolism in vivo (13). Epidemiological studies have further suggested that ß-cryptoxanthin constitutes a sustainable nutritional approach to improving the bone health of human subjects (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%